Pengaruh Media Pembelajaran Interaktif Terintegrasi PBL terhadap Peningkatan Kemampuan Berpikir Kritis pada Materi Sistem Ekskresi: (The Effect of Integrated PBL Interactive Learning Media on Improving Critical Thinking Skills in Excretory System Material) - Priani, Nurul Kholiza; Hutagaol, Jeklin; Siregar, Khofifa Romaito; Jumiah , Jumiah (BIODIK, 2025)
Critical thinking is very popular in education, and its learning refers to reasoning, analyzing, problem-solving strategies, and finding solutions. Critical thinking is very important for students, but in reality, students' critical thinking skills are still low. The use of appropriate learning models can improve critical thinking, such as the PBL model, which is relevant to learning in the 21st century. The purpose of this study was to examine the effect of integrated interactive PBL learning media on improving critical thinking skills in the subject of the excretory system. This study used a quasi-experiment with a pretest-posttest control group. The sample consisted of two classes, namely the control class (XI MIPA 3) and the experimental class (XI MIPA 1). Data analysis was performed using the T-test. The T-test results with a significance level (2-tailed) < 0.05 showed that there was an effect of integrated PBL learning media on critical thinking skills. Abstrak. Berpikir kritis sangat popular didunia Pendidikan, pembelajarannya mengacu untuk benalar, menganalisis, startegi pemecahan masalah, dan menemukan solusi. Berpikir kritis sangat penting bagi peserta didik, tapi kenyataannya berpikir kritis peserta didik masih tegolong rendah. Tujuan penelitian untuk melihat pengaruh media pembelajaran interaktif terintegrasi PBL tehadap peningkatan kemampuan berpikir kritis pada materi sistem ekskresi. Penelitian ini menggunakan Quasy exsperiment dengan pretest-posttest control grup. Sampel dua kelas yaitu kelas kontrol (XI MIPA 3) dan eksperiment (XI MIPA 1). Analisis data menggunakan uji T. Hasil uji T dengan signifikasi (2-tailed) < 0,05 yang menunjukan adanya pengaruh media pembelajaran terintegrasi PBL terhadap kemampuan berpikir kritis.